Stress appraisals, emotions, and coping among international adolescent golfers - Nicholls, A. R.; Hemmings, B.; Clough, P. J. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The aims of this study were to (a) explore the emotions generated during or as a consequence of stress appraisals, after coping, and after the event outcome, (b) explore whether multiple emotions were generated from the initial stress appraisal through to event outcome, and (c) to explore whether outcomes that were perceived as favorable resulted in positive emotions and outcomes that were perceived as unfavorable or neither favorable nor unfavorable resulted in negatively toned emotions. Participants were 10 male English international adolescent golfers (mean±SD; age 16.7±1.6 years), who were interviewed regarding their experiences of stress appraisals, emotions, and coping during competitive golf. Results revealed that emotions were generated within or as a consequence of stress appraisals, after coping, and after the event outcome. Additionally, multiple emotions were generated from the stressful appraisal to the event outcome. Positively toned emotions were cited more frequently than negatively toned emotions after favorable events, whereas negatively toned emotions were reported more frequently than positively toned emotions after unfavorable events. Coping appears important in generating positively toned emotions.